Polyanhydride Nanovaccine Induces Robust Pulmonary B and T Cell Immunity and Confers Protection Against Homologous and Heterologous Influenza A Virus Infections - Zacharias, Zeb R.; Ross, Kathleen A.; Hornick, Emma E.; Goodman, Jonathan T.; Narasimhan, Balaji; Waldschmidt, Thomas J.; Legge, Kevin L. (Frontiers in Immunology, 2018)
Influenza A virus (IAV) is a major cause of respiratory illness. Given the disease severity, associated economic costs, and recent appearance of novel IAV strains, there is a renewed interest in developing novel and efficacious “universal” IAV vaccination strategies. Recent studies have highlighted that immunizations capable of generating local (i.e., nasal mucosa and lung) tissue-resident memory T and B cells in addition to systemic immunity offer the greatest protection against future IAV encounters. Current IAV vaccines are designed to largely stimulate IAV-specific antibodies, but do not generate the lung-resident memory T and B cells induced during IAV infections. Herein, we report on an intranasally administered biocompatible polyanhydride nanoparticle-based IAV vaccine (IAV-nanovax) capable of providing protection against subsequent homologous and heterologous IAV infections in both inbred and outbred populations. Our findings also demonstrate that vaccination with IAV-nanovax promotes the induction of germinal center B cells within the lungs, both systemic and lung local IAV-specific antibodies, and IAV-specific lung-resident memory CD4 and CD8 T cells. Altogether our findings show that an intranasally administered nanovaccine can induce immunity within the lungs, similar to what occurs during IAV infections, and thus could prove useful as a strategy for providing “universal” protection against IAV.